2008
DOI: 10.1021/om8006147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Three New N-Heterocyclic Silylenes

Abstract: di-tert-butyl-4-methyl-1,3-diaza-2-silacyclopentane-2-ylide (7), haVe been synthesized by the reaction of their corresponding dibromides with KC 8 . Unlike the analogous silylene 2, which lacks any backbone substitution and tetramerizes in concentrated solution or as a solid, silylenes 5, 6, and 7 show no tendency to oligomerize. The reactions of 5 with tert-butanol and chloroalkanes giVe only 1:1 O-H or C-Cl insertion products; with adamantyl azide 5 yields the spirosilatetrazoline 8, while with mesityl azide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…In the 29 Si NMR spectrum, ad oublet of doublets appears significantly downfield (d = 302 ppm, J SiRh = 34.7 Hz, J SiP3 = 26.5 Hz) compared to that observed for the precursor 4 (d = 21.7 ppm, dddd, J SiRh = 92.3 Hz, J SiP = 214.2, 50.2, and 23.8 Hz), which is in good agreement with at wo-coordinate silylene moiety in 5.This signal is also considerably downfield compared to the chemical shifts of NHSi species II-V (d = 78-213 ppm), [11][12][13][14][15][16] but falls in the range of cyclic (amino)-(bora-ylide)silylene VI (d = 296 ppm), [17] cyclic alkyl-(amino)silylene VII (d = 275 ppm), [18] and dithiolate silylene (d = 285 ppm). In the 29 Si NMR spectrum, ad oublet of doublets appears significantly downfield (d = 302 ppm, J SiRh = 34.7 Hz, J SiP3 = 26.5 Hz) compared to that observed for the precursor 4 (d = 21.7 ppm, dddd, J SiRh = 92.3 Hz, J SiP = 214.2, 50.2, and 23.8 Hz), which is in good agreement with at wo-coordinate silylene moiety in 5.This signal is also considerably downfield compared to the chemical shifts of NHSi species II-V (d = 78-213 ppm), [11][12][13][14][15][16] but falls in the range of cyclic (amino)-(bora-ylide)silylene VI (d = 296 ppm), [17] cyclic alkyl-(amino)silylene VII (d = 275 ppm), [18] and dithiolate silylene (d = 285 ppm).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In the 29 Si NMR spectrum, ad oublet of doublets appears significantly downfield (d = 302 ppm, J SiRh = 34.7 Hz, J SiP3 = 26.5 Hz) compared to that observed for the precursor 4 (d = 21.7 ppm, dddd, J SiRh = 92.3 Hz, J SiP = 214.2, 50.2, and 23.8 Hz), which is in good agreement with at wo-coordinate silylene moiety in 5.This signal is also considerably downfield compared to the chemical shifts of NHSi species II-V (d = 78-213 ppm), [11][12][13][14][15][16] but falls in the range of cyclic (amino)-(bora-ylide)silylene VI (d = 296 ppm), [17] cyclic alkyl-(amino)silylene VII (d = 275 ppm), [18] and dithiolate silylene (d = 285 ppm). In the 29 Si NMR spectrum, ad oublet of doublets appears significantly downfield (d = 302 ppm, J SiRh = 34.7 Hz, J SiP3 = 26.5 Hz) compared to that observed for the precursor 4 (d = 21.7 ppm, dddd, J SiRh = 92.3 Hz, J SiP = 214.2, 50.2, and 23.8 Hz), which is in good agreement with at wo-coordinate silylene moiety in 5.This signal is also considerably downfield compared to the chemical shifts of NHSi species II-V (d = 78-213 ppm), [11][12][13][14][15][16] but falls in the range of cyclic (amino)-(bora-ylide)silylene VI (d = 296 ppm), [17] cyclic alkyl-(amino)silylene VII (d = 275 ppm), [18] and dithiolate silylene (d = 285 ppm).…”
supporting
confidence: 80%
“…[16,17] This value is even larger than those observed for the acyclic monoaminosilylenes with ab ulky boryl (XII) or as ilyl substituent (XIII; 109.5-116.98 8). TheN 1 À Si1 bond length [1.758 (3) ]i ss imilar to those observed in cyclic diaminosilylenes (1.719-1.753 ) [11][12][13] and considerably shorter than those of phosphonium ylide substituted silylenes V (1.797 )a nd VI (1.814 ), which are particularly elongated due to the much stronger p-donation of the ylide substituents toward the silicon atom compared to the amino group. TheN 1 À Si1 bond length [1.758 (3) ]i ss imilar to those observed in cyclic diaminosilylenes (1.719-1.753 ) [11][12][13] and considerably shorter than those of phosphonium ylide substituted silylenes V (1.797 )a nd VI (1.814 ), which are particularly elongated due to the much stronger p-donation of the ylide substituents toward the silicon atom compared to the amino group.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Stable silylenes 1-8 [1][2][3][4][5][6][7][8][9][10][11] are known for several years and most of the well-characterized examples are N-heterocyclic silylenes (NHSi), in which the di-coordinated silicon atom is substituted by two nitrogen atoms. Although the synthesis of NHSis 1 [1], 2a [2], 3a [4] were reported already 15 years ago, the chemistry of these compounds and their use in synthesis is still very limited, in particular when compared with the analogous N-heterocyclic carbenes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the synthesis of the first stable N-heterocyclic silylene (NHSi)i n1 994 by West et al [1] ap lethora of stable NHSi compounds have been reported. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] They are generally stabilized kinetically using sterically demanding substituents and electronically through p-donation of the lone pair of electrons of nitrogen into the empty 3p orbitala tt he divalent silicon atom. [16] In 1998, Kira et al reported the synthesis of an acyclic bis(diisopropylamino)silylene, which is generatedp hotochemically and could only be detected in low concentrateds olutions by 1 HNMR and UV/Vis spectroscopy and by trapping experiments.…”
mentioning
confidence: 99%